Siro : Studies in radicalism online - Michigan State University - Libraries (2021)
"SiRO (Studies in Radicalism Online) is a scholarly organization devoted to forging links between the material archive of resources for the study of radicalism and the digital research environment. The activities of this effort are driven by three primary goals: [1] to provide a virtual community for those engaged in the study of radicalism and [2] to meet emerging needs of this community, including making recommendations on technological and scholarly standards for electronic scholarship, the aggregation of data, and the ability to discover and repurpose this data, and [3) to aggregate resources (both primary and secondary) relevant to radicalism studies." [self-description]